Savaş Alanları Turizmine Yönelik Motivasyon, Duygu ve Deneyimler: Metristepe ve İnönü Şehitlikleri-Bozüyük Örneği - Ayşe Okuyucu; Feridun Erol (Coğrafi Bilimler Dergisi, 2018)
The war is one of the great tragedies of human history. Today, the areas are devastated by war are seen as a resource for trigger the tourism. Battlefields, martyrdoms, monuments, museums and historical shows create an attractiveness for dark tourism. However, there is a limited literature about motivation sources of battlefields area visits. Bilecik where the foundation place of the Ottoman Empire also witnessed important events in the War of Independence. The research areas are Metristepe and İnönü war graves where the Battle of Inönü was won. This places located in the Bozüyük district. In the research it was aimed to determine the motivation of people who visited Metristepe and İnönü martyrdom. Qualitative research methods were used in the study. The data were collected in depth interviews held in April and May 2017. A total of 38 people were interviewed and the interviews took about 20-30 minutes. In-depth interview was applied 38 people in total. The data which is collected the research area were analyzed with the MAXQUDA 12 software. Content analysis was applied to determine the motivations of visitors. In addition to this to it was refered in-depth interview in order to understand the issue more deeply. According to the obtained results from the study among the main motivations for visiting the area of participants are memorial ceremony, national feelings, understanding death and martyrdom, history curiosity, having a martyr and veteran soldier in the family. After the visited to the area visitors obtained various learning experince such as learning, understanding the struggle of the motherland, fulfilment spiritual duties and so on. Insufficient transportation opportunity, lack of souvenirs to buy, absence of toilets, resting and sitting areas are among the lacking elements which were observed by visitors in the destination.